2021
DOI: 10.24269/ekuilibrium.v16i1.3184
|View full text |Cite
|
Sign up to set email alerts
|

Wakif's Behavior in Money Waqf: an Approach to Theory of Planned Behavior

Abstract: The Indonesian nation is a country where the development of productive waqf is very potential, but the collection of productive waqf funds, especially cash waqf, has not been optimal. This is thought to be the behavior of the muslim community that does not understand well the development of cash waqf. Based on this phenomenon, this research was conducted to find empirical evidence of the Theory of Planned Behavior and religiosity in influencing the behavior of Muslim communities to conduct cash waqf in Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…Cash waqf regulation in Indonesia provides a lack of justifications in terms of cash waqf supervisory and governance. Those pieces of evidence enhance the facts that cash waqf fails to meet the stakeholders' expectation (Utomo et al, 2020) In addition, according to Iman et al (2021) that attitudes of wakif's, subjective norms, and values of religiosity were able to influence waqf behavior in making decisions to do cash waqf. In fact, according to Nurjannah and Abdullah (2020), cash waqf instruments can be a solution for the economy during the Covid-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Cash waqf regulation in Indonesia provides a lack of justifications in terms of cash waqf supervisory and governance. Those pieces of evidence enhance the facts that cash waqf fails to meet the stakeholders' expectation (Utomo et al, 2020) In addition, according to Iman et al (2021) that attitudes of wakif's, subjective norms, and values of religiosity were able to influence waqf behavior in making decisions to do cash waqf. In fact, according to Nurjannah and Abdullah (2020), cash waqf instruments can be a solution for the economy during the Covid-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 93%
“…As a nation with great potential due to the highest number of Muslim in the world, Indonesia is not left behind when it comes to cash waqf. Iman, Santoso, and Kurniawan (2021) pointed out that the collection of productive waqf funds, specifically cash waqf, has not been ideal. Many assumes the behavior of the Muslim community that does not fully apprehend the improvement of cash waqf.…”
Section: Cash Waqf and Theory Of Planned Behaviormentioning
confidence: 99%
“…Recent studies (Haidlir et al, 2021;Iman et al, 2021;Ismaila & Maryantib, 2022;Osman et al, 2016;Ratnasari et al, 2017) have examined the donor's intention to contribute to waqf. Some of the empirical research (Haidlir et al, 2021;Ismaila & Maryantib, 2022;Osman & Muhammed, 2017;Osman et al, 2016) have adopted TPB and employed SEM and/or PLS in examining the donor's intention to contribute to waqf.…”
Section: Tpb and Intention To Donate To Waqfmentioning
confidence: 99%
“…In summary, there are mixed findings on the effect of ATT, SN, and PBC on donor's intention. Many studies (Alifiandy et al, 2020;Azizi et al, 2019;Haidlir et al, 2021;Iman et al, 2021;Osman & Muhammed, 2017;Pujani et al, 2021;Ratnasari et al, 2017) found a significant positive effect of attitude on donor's intention. However, Ismaila & Maryantib (2022) and Osman et al (2016) could not establish attitude's influential role.…”
Section: Tpb and Intention To Donate To Waqfmentioning
confidence: 99%